2016
DOI: 10.1097/hco.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Improve-It

Abstract: Ezetimibe/simvastatin combination, either as a single pill or as the combined use of the individual compounds, represents a well-tolerated and efficacious choice for dyslipidemia treatment in high-risk subjects, including patients with diabetes. Limited additional risk for adverse events compared with simvastatin monotherapy is observed, and an individualized, patient-centered approach to therapy is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Instead, they create a molecular susceptibility that, in the presence of hypercholesterolemia, increases macrophage cholesterol accumulation, a central event in atherogenesis. From this perspective, obesity/IR can be conceptualized as a perturbation that “sensitizes macrophages to atherogenic lipoproteins,” which may help to explain why type 2 diabetics generally require more aggressive cholesterol lowering to achieve therapeutic benefit ( Banach et al, 2016 ; Hoe and Hegele, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, they create a molecular susceptibility that, in the presence of hypercholesterolemia, increases macrophage cholesterol accumulation, a central event in atherogenesis. From this perspective, obesity/IR can be conceptualized as a perturbation that “sensitizes macrophages to atherogenic lipoproteins,” which may help to explain why type 2 diabetics generally require more aggressive cholesterol lowering to achieve therapeutic benefit ( Banach et al, 2016 ; Hoe and Hegele, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In epidemiological studies, traditional risk factors, such as smoking, hypertension, low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, total cholesterol, and triglyceride levels, do not explain the risk associated with CVD in type 2 diabetic patients ( Beckman et al, 2002 ; Gore et al, 2015 ; Haffner et al, 1998 ; Hayward et al, 2015 ). Moreover, intervention studies showed that increased mortality is observed even when plasma cholesterol levels are aggressively lowered with statin treatment, hypertension is controlled, or with aggressive glycemic control ( Banach et al, 2016 ; Gore et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it needs to be noted that lipid profiling should be performed every 6–8 weeks until the achievement of target concentrations of different lipid fractions. The common practice in outpatient treatment, however, is based on fixed doses of statins without biochemical monitoring of treatment results [6, 32, 168]. …”
Section: Causes Of Ineffective Treatment Of Dyslipidaemiasmentioning
confidence: 99%